Penggunaan Media Game Gamilab Pada Mata Pelajaran IPAS Untuk Meningkatkan Hasil Belajar Peserta Didik Kelas V SDN Gambut 1 - Sadiyah, Halimatus; J, Jumiati; Ansari, Muhammad Iqbal (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study was designed to identify the extent to which the utilization of gaming media from Gamilab on the subject of Natural and Social Sciences (IPAS) can improve the learning achievement of gradeV students in SDN Gambut1. as research subjects. In the preliminary observation phase, teachers using Gamilab media obtained an activity score of 78.75% in cycleI.After being given the opportunity to improve their teachingpractice and integrate games more intensively, the score rose to 89.30% in cycleII. The comparison of mean?scores of students between cycleI and cycleII showed a significant improvement; in cycleI the mean?value recorded was 63%, while in cycleII it increased to 78%, signifying an increase of 15 percentage points. Further, the written test pass rate also showed growth: in cycleI only 70% of students achieved graduation standards, however in cycleII this figure jumped to 87%, signifying an increase of 17%. From the findings it can be concluded that the integration of Game Gamilab media in the learning?teaching process of IPAS positively impacts the quality of learning, improves teacher engagement, lifts students academic achievement, as well as increases the percentage of successfully qualified learners.